Correlation between spirometric findings and 6-min walk test in patients with chronic obstructive pulmonary disease - Sudha S; Vijiyalakshmi V; Vikash Sharma; Sai Sailesh Kumar Goothy (Asian Journal of Medical Sciences, 2025)
Background: Chronic obstructive pulmonary disease (COPD) is characterized by permanent respiratory symptoms and limitation of airflow which is due to airway and/or alveolar abnormalities, caused by significant exposure to noxious particles or gases. COPD is a common, preventable, and treatable disease. The present study was undertaken to correlate the spirometric values with the result of 6MWT and to assess whether 6MWT can be used as an alternative test to spirometry in predicting the severity of COPD. Aims and Objectives: The present study observed correlate the spirometric values with result of 6-min walk test (6MWT). Materials and Methods: A total of 40 male and female COPD patients within the age group of 25–75 years of were part of the study. Spirometric indices forced expiratory volume 1 s(FEV1), %FEV1, forced vital capacity (FVC), FEV1/FVC ratio were recorded. Soon after the spirometry, the subjects were subjected to 6MWT. 6MWT was performed on a 30 m stretch. Distance walked in 6 min was recorded in meters. Predicted 6-min walk distance (6MWD) (For males)=561.022-(2.507×age years)+(1.505×weight kg)-(0.055×height cm) Predicted 6-min walk distance(for females)=30.325–(0.809×age years)-(2.074×weight kg)+(4.235×height cm) Patients were divided into normal (> 80%), mild impairment (60–79%), moderate impairment (40–59%), and severe impairment (<40%). Results: Out of 40 participants, there were 15 females and 25 male participants. In age group of 25–35 years -2 males, 36–45 years-9 patients (6 females and 3 males), 46–55 years -10 cases (5 females and 5 males), 56–65 years -13 patients (3 females and 10 males), 66–75 years- 6 patients(1 female and 5 males. Correlation of 6MWD with FEV1 (P=0.00026), FEV1% predicted (P=0.000), FVC (P=0.00096), FEV1/FVC (0.001). Correlation of % predicted 6MWD with FEV1 (P=0.001), FEV1 %predicted (P=0.000), FVC (P=0.002), FEV1/FVC (0.006). There is significant positive correlation of 6MWD and % predicted 6MWD with FEV1, FEV1 predicted value, FVC, and FEV1/FVC. Conclusion: The study results provide additional evidence that the 6MWT is a simple reproducible, inexpensive test to assess the patient’s functional capacity in the south Indian population. Further detailed studies are recommended in this area.